Hubungan Dinamika Kelompok Tani dengan Produktivitas Ubi Jalar Cilembu - Marliana, Lina; Tridakusumah, Ahmad Choibar (Hasanuddin University, 2024)
This research aims to determine the level of group dynamics and the level of productivity of Cilembu sweet potatoes in the Harapan Mulya Farmers Group, as well as the relationship between group dynamics and the level of productivity of Cilembu sweet potatoes in the Harapan Mulya Farmers Group. The type of research used is mixed method with survey methods. The data analysis used is scoring analysis, Spearman rank correlation analysis, and descriptive analysis. The group dynamics were measured using a standardized questionnaire that assessed factors such as communication, decision-making, and conflict resolution. Respondents in the study were determined using a random sampling technique, and a total of 48 respondents were obtained using the Slovin formula. The research results show that the level of group dynamics in the Harapan Mulya Farmers Group is in the dynamic category, with a total score of 6,789 and a percentage of 74%. The productivity of Cilembu sweet potato farming in the Harapan Mulya Farmer Group is quite high, with a productivity interval of 9.42 - 11.27 tons/ha. The research results show that there is a significant relationship between group dynamics and the productivity of Cilembu sweet potato farming with a significance value of 0.014 and a correlation coefficient of 0.351, which means that the relationship between group dynamics and the productivity of Cilembu sweet potato farming is correlated with a fairly strong correlation strength the relationship between the two variables is in the same direction.